Consumer preferences, and willingness to pay for safe pork products in rural Kenya - Gichuyia, Cianjo M.; Mtimet, Nadhem; Fèvre, Eric M.; Thomas, Lian F.; Gathura, P.; Onono, J.O.; Akaichi, F. (Elsevier, 2024)
Designing interventions to support the safe development of rapidly growing livestock value chains in sub-Saharan Africa requires a clear understanding of consumer demands. This study aimed to determine purchase patterns, consumers' preferences, and willingness to pay for safe pork attributes; specifically, the presence of a veterinary inspection stamp and the cleanliness of the butchery.